464 Hospital Frailty Risk Score and Healthcare Resource Utilization After Surgery for Metastatic Spinal Column Tumors. (1st April 2022) - Elsamadicy, Aladine A.; Koo, Andrew B.; Reeves, Benjamin; Pennington, Zach; Yu, James; Goodwin, C. Rory; Kolb, Luis; Laurans, Maxwell S. H.; Lo, Sheng-fu L.; Shin, John H.; Sciubba, Daniel
Abstract : INTRODUCTION: The Hospital Frailty Risk Score (HFRS) was recently developed utilizing ICD-10 diagnostic codes to identify frailty and predict adverse outcomes in large national database studies. While other studies have examined frailty in spine oncology, HFRS has not been assessed in this patient population. METHODS: A retrospective cohort study was performed using the National Inpatient Sample (NIS) database from the years 2016 to 2018. All adult patients (=18 years-old) undergoing surgery metastatic spinal column tumor were identified using the ICD-10-CM diagnostic and procedural coding systems. Patients were categorized into two cohorts based on the criteria of the HFRS: No Frailty (HFRS <5) and Frail (HFRS = 5). A multivariate logistic regression analysis was used to identify independent predictors of prolonged LOS, non-routine discharge, and increased cost. RESULTS: Of the 8, 500 patients identified, 3, 230 (38.0%) were found to be Frail by HFRS criteria. Compared to the Non-Frail cohort, the Frail cohort was found to have a significantly longer LOS (Non-Frail: 7.9 ± 5.0 vs Frail: 14.8 ± 13.0, p < 0.001), a significantly higher rate of Non-Routine discharge (Non-Frail: 639.8% vs Frail: 61.7%, p = 0.001), and a significantly greater mean total cost of hospital admission (Non-Frail: $48, 108 ± $29, 654 vs Frail: $66, 798 ± $45, 712, p < 0.001). On multivariate regression analysis, Frailty was found to be a significant predictor of both prolonged LOS [OR: 4.02, CI (3.06, 5.27), p < 0.001] and non-routine discharge [OR: 2.13, CI (1.68, 2.71), p < 0.001]. CONCLUSION: Our study is the first to use the HFRS to assess the impact of frailty on patients with metastatic bony spinal tumors. We found that in this patient population, Frailty was associated with prolonged hospital LOS, non-routine discharge and total hospital costs.